Hornhautvernetzung mit Riboflavin und UV-A-Licht bei Keratokonus - Raiskup, Frederik; Terai, N; Veliká, V; Spörl, E (Klinische Monatsblätter für Augenheilkunde, 2016)
Changes in the biomechanical properties of the human cornea play an important role in the pathogenesis of corneal ectatic diseases. Many different pathological conditions in the cornea may reduce its biomechanical resistance. Corneal collagen cross-linking (CXL) has emerged as a promising technique to slow or even to stop the progression of ectasia. In this procedure, riboflavin (vitamin B2) is administered in conjunction with ultraviolet A light (UVA, 365 nm). This interaction causes the formation of reactive oxygen species, leading to additional covalent bonds between collagen molecules, with consequent biomechanical stiffening of the cornea. Although this method is not yet accepted as an evidence-based treatment of corneal ectasia, the results of prospective, randomised studies of CXL used in the treatment of this pathological entity show significant changes in the properties of corneal tissue. This procedure is currently the only aetiopathogenetic treatment of ectatic eyes that can delay or stop the process of cornea destabilisation, reducing the necessity for keratoplasty. Despite promising results, CXL is associated with issues that include long-term safety and duration of the stabilising effect.
Keywords: výsledek terapie; rohovka; Keratoconus; Cornea; lidé; Photochemotherapy; riboflavin; Ultraviolet Therapy; Photosensitizing Agents; Treatment Outcome; Cross-Linking Reagents; fotosenzibilizující látky; reagencia zkříženě vázaná; medicína založená na důkazech; terapie ultrafialovými paprsky; fotochemoterapie; keratokonus; Evidence-Based Medicine; Riboflavin; Humans